Pioneers of psychology - Fancher, Raymond E. (New York : W. W. Norton, 1996)
This book presents about: the Foundations of Modern Psychology; Philosophers of Mind; The Sensing and Perceiving Mind; the Theory of Evolution; the Measurement of Mind; Psychology as the Science of Behavior...
Keywords: History; Psychology; Psychology -- History; Psychologists -- History